STUDY ONTHE LIPID DISTRIBUTION PATTERN IN MUSCLES OF TWO TELEOSTS, ARJUS DUSSUMIERI AND OPHIOCEPHALUS STRJATUS - ALEXANDER, K M (Fishery Technology, 2025)
The distribution of total lipids in different parts of the body of A. dussumieri and 0. Sfriatus has been studied and reported in this Paper